2015
DOI: 10.3923/jms.2015.241.245
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diabetic Property and Phytochemical Composition of Aqueous and Methanol Extracts of Buchholzia coriacea Seeds in Alloxan-Induced Diabetic Rats

Abstract: is an International, peer-reviewed scientific journal that publishes original article in experimental & clinical medicine and related disciplines such as molecular biology, biochemistry, genetics, biophysics, bio-and medical technology. JMS is issued eight times per year on paper and in electronic format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The increase in BMG, FER and PER observed in 2.5% VA groups treated group may be attributed to the antidiabetic potential of BC [9].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The increase in BMG, FER and PER observed in 2.5% VA groups treated group may be attributed to the antidiabetic potential of BC [9].…”
Section: Discussionmentioning
confidence: 77%
“…The seed is used as aphrodisiac in Cameroon, childbirth enhancer in Ivory Coast and antidiabetic agent in Nigerian ethnomedical practice. The antiulcer, analgesic, antidiabetic, anthelminthic, antibacterial, anti-inflammaory and antioxidant activities of B. coriacea have been reported [3][4][5][6][7][8][9]. There is paucity of information on the effects of Buchholzia coriacea on nutrient utilization and clinical biochemical parameters in alloxan-induced diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical screening of Buchholzia coriacea seeds has shown that the seeds are rich in alkaloids, tannins, flavonoids, and saponins (Mbata, Duru, Onwumelu, 2009;Obiudu et al, 2015). Many medicinal plants with antibacterial and anti-malarial properties, which have been reported to be rich in these phytochemicals, are also reputed to have antifertility actions (Gupta, Sharma, 2006).…”
Section: Introductionmentioning
confidence: 99%